Analysis of Indonesia's Constitutional System in Overcoming The Lame Duck Session Period After The General Election (Case Study: Legislation Productivity of Legislative Institution in Indonesia) - Muhammad Ulil Absor; Muhammad Zaki Mubarrak (LEGAL BRIEF, 2024)
This study discusses specifically about the Lame Duck Session period that occurred in Indonesia, Lame Duck can be said to be a situation where officials who are not re-elected but still sit in office until new officials are sworn in, the phenomenon arises because of a long time lag between polling day to inauguration day. this research aims to find out and analyze specific rules, as well as the political strategy of state law in overcoming and controlling the Lame Duck Session after the general election. The method used in this research is a type of normative legal research with a statutory approach and comparative legal sourced from secondary data, literature data by being analyzed qualitatively. The urgency of legal regulation regarding Lame Duck Session in Indonesia needs to be regulated, especially in the constitution of the 1945 Constitution, this is because there is no clear regulation compared to several other countries that have been contained in the highest constitution. However, in the constitutional system, not only law but politics or power is also an important instrument in the formation and exploration of law, especially in the constitutional law system to overcome a phenomenon such as the Lame Duck Session